Automatic watering plant system - Saharudin, Muhammad Fakhrullah (2025)
The automatic watering plant system is designed to address the challenge of maintaining optimal soil moisture levels for plant health in a convenient and efficient manner. Traditional methods of manual watering are often inefficient, leading to either overwatering or underwatering, which can harm plant growth and sustainability. The objective of this project is to develop an automated system that ensures plants receive the right amount of water based on real-time soil moisture data. To achieve this, the system integrates a series of sensors, microcontrollers, and actuators. Soil moisture sensors are deployed to continuously monitor the moisture content in the soil. These sensors relay data to a microcontroller, which processes the information and determines when watering is necessary. An irrigation system, controlled by the microcontroller, is activated to deliver water to the plants when the soil moisture falls below a pre-defined threshold. Additionally, environmental sensors such as temperature and humidity sensors may be used to further refine the watering schedule. The methodology involves designing the sensor network, programming the microcontroller for data processing and control logic, and implementing the irrigation system. The project includes phases of prototyping, testing, and iterative refinement to ensure reliability and efficiency. The expected result is a fully functional automatic watering system that minimizes water wastage, reduces the need for manual intervention, and promotes healthier plant growth. By maintaining optimal soil moisture levels, the system aims to enhance the sustainability of plant care practices and contribute to water conservation efforts.